Legal Accents, Legal Borrowing : The International Problem-Solving Court Movement - Nolan, James L., Jr (Book collections on Project MUSE., 2009)
A wide variety of problem-solving courts have been developed in the United States over the past two decades and are now being adopted in countries around the world. These innovative courts--including drug courts, community courts, domestic violence courts, and mental health courts--do not simply adjudicate offenders. Rather, they attempt to solve the problems underlying such criminal behaviors as petty theft, prostitution, and drug offenses. Legal Accents, Legal Borrowing is a study of the international problem-solving court movement and the first comparative analysis of the development of these courts in the United States and the other countries where the movement is most advanced: England, Scotland, Ireland, Canada, and Australia.